Complete genomic analysis of uncommon G12P[11] rotavirus causing a nosocomial outbreak of acute diarrhea in the newborns in New Delhi, India. Issue 6 (2nd December 2021) - Ranshing, Sujata; Ganorkar, Nital; Ramji, Siddarth; Gopalkrishna, Varanasi
Abstract: Rotaviruses (RVs) are the major causative agents of acute gastroenteritis in children, but in neonates, RV infections are generally nosocomial in origin and mostly asymptomatic. However, there have been infrequent reports of nosocomial outbreaks of clinical disease in this population. In this study, we describe uncommon RV genotype; G12P[11] associated with an outbreak of acute gastroenteritis in the neonatal ward and neonatal intensive care unit (NICU) in New Delhi, North India. Full‐genome analyses of the pathogenic G12P[11] strain was carried out to map the genotype constellation and further to explore the variations in the antigenic epitopes on the immunodominant VP7 and VP4 proteins, the amino acid sequences were compared with neonatal strains; ROTAVAC® (G9P[11]) and asymptomatic G12P[11] and also other G/P‐type matched strains. The study revealed G12–P[11]–I1–R1–C1–M1–A1–N1–T1–E1–H1 human Wa‐like genotype constellation and highlights evidence of gene reassortment. No significant differences were observed in the sequences of structural (except VP3) and nonstructural encoding genes of G12P[11] strains recovered from symptomatic and asymptomatic neonates. Presence of additional N‐linked glycosylation site was noted in the G12 strains, as a consequence of a change from Asp→Asn at amino acid position 238. Interestingly, only two and four amino acids substitution within the 7‐1a and 8‐1 antigenic epitope were observed, respectively, compared with asymptomatic G12P[11] strain. The study emphasizes the importance of close monitoring of RV outbreaks in neonates for early alarming of novel strain. Highlights: Uncommon RV genotype, G12P[11] reported in an outbreak of acute gastroenteritis in neonates. G12P[11] exhibited Wa‐like genotype constellation Strain might have undergone gene reassortments No significant differences observed in structural (except VP3) and non‐ structural genes of G12P[11] strains in symptomatic and asymptomatic neonates. N‐linked glycosylation site was noted in G12 strain.